The Influence of Digital Payment Adoption, Financial Literacy and Education Level on Financial Management of MSMEs in Makassar - Risma Parmawati; Linda Arisanty Razak (IECON: International Economics and Business Conference, 2024)
This study aims to examine the effect of digital payment adoption, financial literacy, and education level on financial management in Micro, Small, and Medium Enterprises (MSMEs) in Makassar City. With the rapid advancement of the digital era, the use of digital payment systems has become essential for MSMEs to enhance transaction efficiency and security. However, challenges such as low financial literacy and limited understanding of technology among MSME owners still pose significant obstacles to achieving optimal financial management. This study adopts a quantitative approach, utilizing multiple linear regression analysis to explore the relationships between these variables. The research data was collected through surveys administered to MSME owners in Makassar City. The results of the study show that digital payment adoption, financial literacy, and education level all positively influence financial management practices in MSMEs. Specifically, MSMEs that adopt digital payment systems tend to have better financial management practices, which improve their operational efficiency. Additionally, higher financial literacy and education levels enable MSME owners to make more informed financial decisions, further contributing to the overall improvement in financial management. These findings suggest that fostering digital payment adoption, improving financial literacy, and enhancing education levels can significantly support MSMEs in Makassar City in improving their financial management and overall business sustainability.